A study on the intergranular corrosion-fatigue failure of the Zn-Al alloy solenoid valve. (September 2019) - Lachowicz, Marzena Małgorzata
Abstract: The purpose of the performed studies was determining causes of the solenoid valve corrosion which appeared during its operation. As a result of the performed macroscopic observations it has been found that the cause of the corrosion was its unsealing. It led to strong corrosion of the solenoid valve body from its internal surface in the vicinity of the seat as the result of the chloride ions action. This caused covering of its surface with white corrosion products characteristic for zinc alloys. The resulting corrosion was of the intergranular nature and it propagated over grain boundaries and the interdendritic areas leading to decrease in the active cross-section of the part. Highlights: Strong corrosion of the solenoid valve body from its internal surface was found as the result of the chloride ions action. The corrosion propagated over grain boundaries and the interdendritic areas leading to decrease in the active cross-section of the part. Initiation of the corrosion followed in the areas of the α/η interphase boundaries. Dissolution of the η phase in the eutectic areas and near the grain boundaries was observed as results of the galvanic effect.